3D simulation for flood evacuation - Che Mat, Ruzinoor; Abu Bakar, Juliana Aida; Ab. Aziz, Azizi; Yusoff, Mohd Fitri; Noorjasri, Norsyazatul A. (American Scientific Publishers, 2017)
Crowd simulation holds a lot of potential in modelling simulation. Crowd simulation can be used to simulate emergency scenarios without the use of a live human. Crowd simulation may run multiple simulations under variety of conditions which will save time and lower costs in planning, development, and testing of new situations or training modules. Crowd evacuation simulation is conducted by the multi-agent system because many factors were influenced on the crowd simulation during the flood. In addition, the psychological effects of flood victims would be considered to be incorporated into the simulation. Flood disaster is a serious social disaster, which causes a great damage to the society and environment. 3D simulation of flooding process is the significant foundation for the flood evacuation. Hence, this paper discusses the development of 3D Flood Simulation which combines the crowd simulation with human behavior during the flooding. The potential of this application is that it could be used as a training tool for volunteers and emergency personals as well as a tool for planning and assessing designated areas for flood evacuation centre in Malaysia.